The Determination of Flavonoid Components, Total Phenolic Content, and Antioxidant Capacity in Dog Rose (Rosa canina L.) in Lorestan Province - Esfandiar Hassani Moghaddam *; Mahdi Shaaban (Lorestan University of Medical Sciences, 2019)
Background and Aim: Dog rose (Rosa canina L.) is a valuable deciduous shrub, which has long been used for food and medicinal purposes in various parts of the world. This study was laid out for the quantitative determination of the flavonoid components such as kampferol and quercetin, total phenol content and antioxidant capacity in petals and the fruit of the dog rose (Rosa canina L.) ecotype collected in Lorestan province. Materials and Methods: Petals and fruit samples of wild dog rose were harvested in June and September 2014 respectively. The samples were kept in cold box during their transportation to laboratory. Subsequently, the pericarp and seeds were separated and dried at room temperature. The antioxidant capacities of petals and fruits were determined using DPPH method. The flavonoid components, including kampferol and quercetin, were analyzed by high performance liquid chromatography (HPLC). The total phenol and flavonoids were measured using a spectrophotometric device. The results indicate that the amount of total phenol in petals (1957 mg.ml-1) was higher than that of fruits (937 mg.ml-1). The amount of total flavonoid in dog rose petals and fruits were 776 and 450 mg.ml-1 respectively. Results: The antioxidant capacity of dog rose was measured and found to be 9.6% in fruits and 66.7% in petals. However, the fruits contained 141 µg.g-1 of kampferol and petals contained 108 µg.g-1. The measured quercetin in petals (127µg.g-1) was higher than that of fruits (66µg.g-1). In this study, a direct relation was observed between the total phenol and flavonoid contents with antioxidant capacity. Conclusion: The results of this research showed that there are high amounts of total phenol and flavonoid contents, antioxidant capacity and also kampferol and quercetin in petals and fruits of dog rose grown in Lorestan. These results indicated the significance of dog rose in dietary and medical purposes.